Utilización de tres niveles de cascarilla de cacao (5, 10 y 15 %) en la alimentación de conejos mestizos durante el crecimiento y engorde - Paz Jímenez, Patricio Arquímides (2012)
In the Technological Institute Luis A. Martinez, smaller Program of Production Species, Section guinea pigs, located in the parish Celiano Monk, canton Ambato, county of Tungurahua, temperature 14,0 °C, humidity relative 78,00% and precipitation annual 654,0 mm. was evaluated the use of three levels of husk of cocoa (5, 10 and 15%) in the feeding of mestizo rabbits during the growth and put on weight. 32 rabbits of 42 days of age and a weight average of 0,848 Kg were used., distributed totally at random under a design of blocks, in cages of galvanized wire of 0,60 x 0,60 x 0,50 m with a density of 2 rabbits for cage, 4 repetitions were used by treatment. The rabbits were fed twice a day 08H00 and 17H00, the control of weight of the rabbits every 15 days. The study variables, didn't present statistical differences (P> 0,05) among the stockings of the treatments, however, numerically it was observed the biggest final pesos in 15% of husk of cocoa with 2,075 Kg.; the biggest earnings of weight in the levels of husk of cocoa among 1,179 to 1,226 Kg.; to measure of the increment of the levels of husk of cocoa the food consumptions were bigger in a differential range among 9,884 to 10,013 Kg, respectively; the best nutritious conversions in the levels of husk of cocoa among 8,44 at 8,19; in the costs to produce a kilogram of gain of weight in 5% of husk of cocoa with 4,24 dollars; they didn't register low in none of the study treatments; the biggest yields to the channel in the levels of thief's husk among 68,43 to 68,28% and the biggest economic profitabilities, in the levels of husk of cocoa with 1,20 at 1,24 of B/C. In consideration of the reached results, it is recommended to use husk of cocoa until of 15% in the formulation of diets balanced in substitution of matters traditional energy cousins that are scare in certain times of the year (corn, polvillo of rice and wheat bran) to feed rabbits during the stage of growth and put on weight. Describers: husk of cocoa, nutritious conversion, nutritional level, benefit / cost.